MODELING REGULARITIES OF LOCATION AND FORMATION CONDITIONS OF THE GOLD MINING OF THE SOUTH TIAN-SHAN - Isokov M.U. , Maripova S.T. , Movlanov J.J. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article examines the basic elements of modeling the patterns of distribution and formation conditions of gold mineralization in the Southern Tien Shan, which is a segment of the Tien Shan orogenic belt, which stretches in the territories of Uzbekistan, Tajikistan and Kyrgyzstan and further into China along the northern flank of the Tarim and North China platforms to distance 5500 km. In the South Tien Shan, which is the Uzbek segment of the Tien Shan orogenic belt, in three mining regions (Bukatau, Tamdytau, Nurata), unique and large gold deposits are located: Muruntau, Balpantau, Kokpatas, Zarmitan, Guzhumsay and others. All of them were found in open areas. Ore formations of our own gold deposits are gold-rare metal, gold-silver, gold-arsenic, gold-polymetallic. Morphological types: stockworks, sheet-lenticular bodies, systems of core veins, zones of vein-vein mineralization in carbonaceous-terrigenous, volcanogenic-terrigenous intrusive rocks. The exposed parts of the crystalline basement (open areas) within the mountain elevations make up about 17% of the area of the entire territory of Uzbekistan. Their geological knowledge is quite high. But the areas adjacent to the mountain heights covered by the MesoCenozoic cover, including the South Tien Shan, are poorly studied. Therefore, their study is relevant. To study the closed territories in the frame of the basement outcrops, using the maps created in the process of geological exploration works of various years, a map of the thickness of the sedimentary cover was built and the basement map was supplemented with elements of ore content. Prospecting and evaluation criteria for gold mineralization have been established.